Aplikasi Pengelolaan Data Kursus Bahasa Inggris Berbasis Web (Studi Kasus: B-Cil Course) - Sutanto, Giselle Naomi; Wasino, Wasino; Perdana, Novario Jaya (STMIK Banjarbaru, 2024)
English proficiency has become a vital requirement in the globalized era to be competitive in various fields. The Be Communicative and Intelligent Learning Course (B-CIL Course) in Bandar Lampung, formerly known as the Rainbow Course, provides internationally-standard English courses with curricula from Singapore and Australia. Despite operating since 2012, the B-CIL Course still uses a manual system based on Microsoft Excel for student data management, which often leads to data loss and duplication. To address this issue, a web application was designed with features such as registration, student and teacher dashboards, and administrative data management. Through the phases of requirements, design, development, and implementation, this application was created utilizing the Rapid Application Development (RAD) methodology. The findings show that this application may meet user needs while enhancing data accuracy, operational efficiency, and information accessibility for administrators, teachers, and students. Thus, this application helps professors and students monitor schedules and bills, administrators manage data, and potential students who wish to enroll in the course.Keywords: Website; Data management; Registration; CourseÂ AbstrakKemampuan berbahasa Inggris menjadi kebutuhan penting di era globalisasi untuk bersaing di berbagai bidang. Be Communicative and Intelligent Learning Course (B-CIL Course) di Bandar Lampung, yang sebelumnya dikenal sebagai Rainbow Course, menyediakan kursus bahasa Inggris bertaraf internasional dengan kurikulum dari Singapura dan Australia. Meski telah beroperasi sejak 2012, B-CIL Course masih menggunakan sistem manual berbasis Microsoft Excel untuk pengelolaan data siswa, yang sering menyebabkan kehilangan data dan duplikasi informasi. Untuk mengatasi masalah ini, dirancang aplikasi web dengan fitur registrasi, dashboard siswa dan guru, serta manajemen data admin. Kebutuhan, desain, pengembangan, dan implementasi adalah langkah-langkah yang diperlukan untuk pengembangan aplikasi ini melalui metode Rapid Application Development (RAD). Hasilnya menunjukkan aplikasi ini mampu menjembatani kebutuhan users dan meningkatkan efisiensi operasional, akurasi data, serta kemudahan akses informasi untuk siswa, guru, dan admin. Dengan demikian, aplikasi ini memberikan dampak yang baik bagi admin untuk mengelola data, murid serta guru untuk melihat jadwal dan melihat tagihan. Dan bagi calon murid yang ingin mendaftar kursus.Â